RNA-Templated Semiconductor Nanocrystals. - Nan Ma; Dooley, Chad J.; Kelley, Shana O. (Journal of the American Chemical Society, 2006)
The article discusses the use of RNA polynucleotides as nanocrystal ligands and templates. RNA exhibits highly versatile structural properties and conformations that can change dramatically with small changes in sequence. The products of tRNA-templated CdS were characterized by gel electrophoresis and gel filtration chromatography. Organizing nucleotides within the context of a three-dimensional RNA structure facilitates the synthesis of products.